Developing and Evaluating the Psychometric Properties of the Persian Version of Post-traumatic Growth Inventory in Patients With Cancer - Mehdi Heidarzadeh; Mahmood Shamshiri; Maryam Rassouli; Behrouz Dadkhah; Sevda Gardashkhani; Fariba Kazemi Eskandani (Iran University of Medical Sciences, 2021)
Background: Traumatic events could be accompanied by positive personal and psychological changes. However, no scale is available to measure these aspects in patients with cancer. Accordingly, this study aimed at designing and evaluating the psychometric properties of the Persian version of the Post-Traumatic Growth Inventory (P-TGI) in patients with cancer. Methods: According to the quantitative findings of our previous study, 9 items were added to the 21 items of P-TGI. After calculating the Content Validity Index (CVI) and Content Validity Ratio (CVR) coefficients, P-PTGI was finalized with 24 items. A total of 272 eligible patients with cancer who were referred to Shahid Ghazi Hospital in East Azerbaijan Province, Iran for follow-up treatment completed the P-PTGI. The instrument was assessed to determine its construct validity using various indices of Confirmatory Factor Analysis (CFA) and standardized lambda (λ) coefficient, followed by further assessment of the discriminant and convergent validities using the Structural Equation Modeling (SEM). LISREL and SPSS were used for data analysis. Results: According to the results of goodness-of-fit indicators, the 5-dimensional, 24-item P-PTGI model was acceptable. Considering that the values of average variance extracted (AVE=0.53-0.75) were greater than the square of correlation coefficients between the 5 dimensions of P-PTGI, discriminant validity was approved. The convergent validity of the tool was confirmed according to the high lambda standard coefficients (0.50-0.93) between items and their related factors. Additionally, alpha coefficients for 5 dimensions of P-PTGI ranged from 0.84 to 0.93 which confirmed the consistency of the tool. Conclusion: This study revealed that P-PTGI, with 24 items and 5 dimensions, is a valid and reliable tool for assessing PTG in Iranian patients with cancer.